Bank liquidity risk management from micro perspective: a study in oil exporting countries - Ang, Jia Xuan; Ch’ng, Jia Ann; Tan, Pei Wen; Wong, Suet Yee (2021)
Liquidity risk management is important for banks to avoid bank run and maintain its survival in long run. In this study, the data set is panel data and consists of 59 banks in 13 oil exporting countries for the periods of 2014-2018. The data was collected from secondary sources; Bloomberg. Besides, Linear Regression Model has been applied in this study to analyse the relationship between the bank specific factors and liquidity risk. In addition, the panel data with 295 observations has been run by Panel Vector Autoregression (PVAR). In fact, this study is mainly discussed the methods can be used by the banks to manage the liquidity risk from micro perspective. Thus, this study will determine whether there is a significant relationship between the debtor collection period, creditor payment period and liquidity buffer with the liquidity risk in both long term and short term period. The major findings in this study showed that there is a positive relationship between the debtor collection period and liquidity risk in long-term. Meanwhile, there is a negative relationship between the creditor payment period and liquidity buffer with liquidity risk in both short-term and long-term.